1996
DOI: 10.1007/s0021663550002
|View full text |Cite
|
Sign up to set email alerts
|

Mercury adsorption on gold surfaces employed in the sampling and determination of vaporous mercury: a scanning tunneling microscopy study

Abstract: To clarify the mechanism of mercury adsorption on gold surfaces thin epitaxial gold films have been exposed to trace amounts of gaseous mercury under laboratory conditions for different periods of time. The changes in the surface morphology of the thin films caused by the exposure have been studied by scanning tunneling microscopy (STM). The evolution of the surface structures with time has been also investigated, in the course of a few days after the exposure. The adsorption of mercury on the gold surfaces ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 34 publications
1
25
0
Order By: Relevance
“…It has been reported in the literature that, at room temperature, mercury atoms stay only on the top layer or near the surface of the gold surface. [24][25][26][27] At higher temperatures, adsorbed mercury atoms can diffuse into the deeper layers of gold film, up to several nanometers from the surface. 24 Images produced by AFM and scanning-tunneling microscopy ͑STM͒ have shown that some island-like structures are formed on gold surfaces subsequent to mercury exposure.…”
Section: B Surface Adsorption-mercury-gold Systemmentioning
confidence: 99%
“…It has been reported in the literature that, at room temperature, mercury atoms stay only on the top layer or near the surface of the gold surface. [24][25][26][27] At higher temperatures, adsorbed mercury atoms can diffuse into the deeper layers of gold film, up to several nanometers from the surface. 24 Images produced by AFM and scanning-tunneling microscopy ͑STM͒ have shown that some island-like structures are formed on gold surfaces subsequent to mercury exposure.…”
Section: B Surface Adsorption-mercury-gold Systemmentioning
confidence: 99%
“…This operating temperature was chosen following many preliminary experiments in order to reduce the effects of cross contamination from other interferent gas species when detecting Hg 0 vapor while simultaneously reducing the effect of a morphology change that has been reported to occur over long periods of Hg 0 exposure at high operating temperatures closer to 150°C 23 24 . Furthermore, the operating temperature of 101°C is very similar to that used when sampling trace amounts of Hg 0 from industrial flue gas 25 as well as being the temperature at which all Hg 0 is collected by gold coatings in the diffusion screen (stainless steel mesh coated with Au) experiments reported by others 26 .…”
Section: Resultsmentioning
confidence: 99%
“…The operating temperature of 30°C was used, as it was the closest to room temperature which could be controlled by the in-house built mercury vapor delivery system. On the other hand, 75°C was chosen because this was near the temperatures used in field sampling of trace amounts of Hg 0 vapor in industrial effluents 43 and yet lower than the glass-transition temperature of polystyrene (∼100°C) 44 The sensors were tested continuously for a total of 25 days. All sensing measurements were conducted using the following procedure: The experiments were performed in a custom built gas cell, which housed four QCM sensors (Au-MNM modified, Ag-MNM modified, Au-control, and Ag-control), and exposed to a gas stream containing a mixture of dry N 2 and a known concentration of Hg 0 vapor (with or without interferent gases) for 1 h. Thereafter, the sensors were recovered by dry N 2 flow for 1 h without altering the total flow in the gas cell or the operating temperatures.…”
Section: Methodsmentioning
confidence: 99%